2013
DOI: 10.1044/0161-1461(2012/10-0112)
|View full text |Cite
|
Sign up to set email alerts
|

Vocabulary Use Across Genres: Implications for Students With Complex Communication Needs

Abstract: The word lists generated can be used to inform vocabulary selection, organization, and instruction for students with complex communication needs who are beginning writers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
8
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 27 publications
3
8
1
Order By: Relevance
“…Clendon et al (2013) reported 58% overlap in the top 50 most frequently occurring words in their findings compared to the letter writing activities in the McGinnis and Beukelman study (1989). This is similar to the previous study (Clendon & Erickson, 2008), which reported 62% overlap in core words based on the top 50 words in their samples and the letter writing task of McGinnis and Beukelman.…”
Section: Core Vocabulary Of Written Samplessupporting
confidence: 86%
See 3 more Smart Citations
“…Clendon et al (2013) reported 58% overlap in the top 50 most frequently occurring words in their findings compared to the letter writing activities in the McGinnis and Beukelman study (1989). This is similar to the previous study (Clendon & Erickson, 2008), which reported 62% overlap in core words based on the top 50 words in their samples and the letter writing task of McGinnis and Beukelman.…”
Section: Core Vocabulary Of Written Samplessupporting
confidence: 86%
“…Further, there was 56% overlap in the language arts writing task. Clendon et al (2013) reported that 20 out of 50 of the top core vocabulary words matched two other studies’ findings. The distribution of different word types or word choice varied across the studies.…”
Section: Core Vocabulary Of Written Samplessupporting
confidence: 65%
See 2 more Smart Citations
“…For example, a device or picture system should include items particular to the child's home life such as food, toys, and symbols representing holidays or regular events in the child's culture. Further, vocabulary selection in both English and the home language is important because the choice of words can hamper of hinder literacy and language development (Clendon, Sturm, & Cali, 2013). For example, morphological markers and structure words (e.g., auxiliaries, determiners, pronouns) have not traditionally been included on AAC devices, which can negatively affect language and literacy growth for beginning writers in English when their devices contain mostly nouns (Lund & Light, 2007;Sutton, Gallagher, Morford, & Shahnaz, 2000).…”
Section: Cultural Considerations In Assessment and Treatmentmentioning
confidence: 99%